The HIDEOUT Enterprise / Nur Syafiqah Hadirah Hafizo ... [et al.] - Hafizo, Nur Syafiqah Hadirah; Abdul Halim, Najihah; Su’ib, Nur Alisya; Roszlan, Farhanah Athirah; Zaidi, Zaifidatul Shafika (2021)
There are many shops that sell coffee drink in Malaysia, but there are little to no amount of coffee drink shops that sell coffee milk that is healthy to the consumer. So, we are creating and producing coffee milk drinks that are healthier than an average coffee milk by choosing organic brew coffee and buffalo milk as the main ingredients. We also provide drinking service at our café and produce our own coffee buffalo milk. The price is based on the size of the cup. We offered only 2 types of cups which are 550 ml and 300 ml. The price for 300 ml is RM6.50 and RM7.50 for 550 ml. All these prices are affordable because we target all different age could try and buy our coffee milk drinks. We believe that our coffee milk has its own specialty because it is healthier. So that, the consumer will feel better when consume it. Next, we choose Melaka to open our cafe which is located at 129, Jalan Hang Jebat, 75200 Melaka. Starbuck, Mc Donald, Secret Recipe, Tealive, and Chatime were all our competitors which are not far away from our cafe. All of them have their own strength and specialty. To expand and promote the coffee buffalo milk drinks than others competitor, we prepare interesting packaging, and a lots of promotion such as buy 2 free 1. Next, social media such Instagram, Facebook, Twitter and TikTok plays an important roles and used to viral the advertisement about our coffee buffalo milk drinks. Then, by using printed media likes business card and flyers can make people know better about our drinks. Lastly, outdoor advertisement such as signboard that placed in front of the cafes is one of the initiatives to make it easier for customer to recognize and come to the cafe. Furthermore, personal selling also our sales promotion. It is an effective strategy by using word of mouth marketing because we can attract and meet face to face with the customer. Hence, it helps increasing the sales easily. Lastly, we believe and confident that this business can go further to succeed and expand to the higher level because it has its own special which is healthy coffee milk drinks. Plus, suitable for any generation to buy it and share with other people because the price offered is really affordable. Also, we provide 100% satisfaction to our customers of excellent services among other competitors. Last but not least, our coffee buffalo milk drinks is different than other coffee milk. So, we believe that our drink could reach target market and able to maintain the performance by providing highest quality coffee buffalo milk drinks, as well as keeping the customers happy.